2021
DOI: 10.1177/10946705211061190
|View full text |Cite
|
Sign up to set email alerts
|

Unintended Consequences in Transformative Service Research: Helping Without Harming

Abstract: Even as transformative service initiatives promote greater well-being, they may also create unintentionally negative consequences. Research investigates boundary conditions and boomerang effects that wash out or reverse the intended effects of service initiatives. However, such research generally advances greater depth of insight about unintended consequences in a particular stream rather than bridging this knowledge across service domains. Thus, service research lacks integrative frameworks, theory, and empir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…Firstly, findings obtained within the service actor perspective changes theme identified that several social factors can influence employee perceptions towards exoskeleton adoption within a workforce. If these social factors are not sufficiently addressed by managers during the implantation of exoskeletons, these factors may trigger unintended consequences within the service setting and disrupt value transactions within the larger service ecosystem (Blocker et al , 2022). For instance, managers must provide exoskeletons to employees on a fully opt-in basis to address potential service actor agency trade-off issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, findings obtained within the service actor perspective changes theme identified that several social factors can influence employee perceptions towards exoskeleton adoption within a workforce. If these social factors are not sufficiently addressed by managers during the implantation of exoskeletons, these factors may trigger unintended consequences within the service setting and disrupt value transactions within the larger service ecosystem (Blocker et al , 2022). For instance, managers must provide exoskeletons to employees on a fully opt-in basis to address potential service actor agency trade-off issues.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, service managers must also anticipate changes to the servicescape and workspace layout. To fully leverage the value-enhancing potential of exoskeleton technologies within existing service ecosystems, service design considerations must ensure that exoskeletons can be fully integrated without causing unforeseen consequences for the employee or value creation process (Blocker et al , 2022). To avoid such unforeseen consequences and/or detrimental outcomes, service delivery testing and usage of grounded technology rules (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…By showing that firms rely not only upon distinct value propositions with a focus on economic and utilitarian value but also on meaningful ones with a focus on the hedonic and transformative value of service system smartness, this research augments the relevance of transformative service research (e.g., Anderson and Ostrom 2015; Ostrom et al 2021) and better marketing for a better world (Chandy et al 2021). Indeed, as stated by Blocker et al (2022), firms seem to anticipate unintended and harmful consequences of service system smartness, thereby urging them to communicate about how their smart service system contributes to well-being. As such, firms can help customers to improve their well-being when crafting or connecting different smart service systems, such as in a smart home (Harvey et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Especially because marketing academics are increasingly interested in the idea of “better marketing for a better world” (Chandy et al , 2021), the unintended impact of our efforts must be better understood; to date, they remain largely unexplored. Focusing on unintended consequences is a catalyst for research that is likely to generate richer and more comprehensive frameworks about the impact of well-being-focused marketing research over time (Blocker et al , 2022 for a more detailed discussion).…”
Section: Cautionary Reflections: the Ethics Of Impact And Unintended ...mentioning
confidence: 99%